Fecal carriage of extended-spectrum β-lactamase-producing Enterobacteriaceae in hospital and community settings in Chad - Ouchar Mahamat, Oumar; Tidjani, Abdelsalam; Lounnas, Manon; Hide, Mallorie; Benavides, Julio; Somasse, Calèbe; Ouedraogo, Abdoul-Salam; Sanou, Soufiane; Carrière, Christian; Bañuls, Anne-Laure; Jean-Pierre, Hélène; Dumont, Yann; et al. (Antimicrobial resistance & infection control, 2019)
Fecal carriage of extended-spectrum β-lactamase-producing (ESBL-PE) remains poorly documented in Africa. The objective of this study was to determine the prevalence of ESBL-PE fecal carriage in Chad. In total, 200 fresh stool samples were collected from 100 healthy community volunteers and 100 hospitalized patients from January to March 2017. After screening using ESBL-selective agar plates and species identification by MALDI-TOF mass spectrometry, antibiotic susceptibility was tested using the disk diffusion method, and ESBL production confirmed with the double-disc synergy test. The different ESBL genes in potential ESBL-producing isolates were detected by PCR and double stranded DNA sequencing. phylogenetic groups were determined using a PCR-based method. ESBL-PE fecal carriage prevalence was 44.5% (51% among hospitalized patients vs 38% among healthy volunteers; < 0.05). ESBL-producing isolates were mostly (64/89) and (16/89). PCR and sequencing showed that 98.8% (87/89) of ESBL-PE harbored genes: in 94.25% (82/87) and - in 5.75% (5/87). Phylogroup determination by quadruplex PCR indicated that ESBL-producing isolates belonged to group A ( = 17; 27%), C ( = 17; 27%), B2 ( = 9; 14%), B1 ( = 8; 13%), D ( = 8; 13%), E ( = 1; 1.6%), and F ( = 1; 1.6%). The ST131 clone was identified in 100% (9/9) of B2 strains. The high fecal carriage rate of ESBL-PE associated with CTX-M-15 in hospital and community settings of Chad highlights the risk for resistance transmission between non-pathogenic and pathogenic bacteria.